Representations of Ɗ-kinds - Drozd , Yu. A.; Izyumchenko , L. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A criterion for module boundedness of a certain class of semihereditary rings — tensor algebras of Ɗ-form — is given.